2015
DOI: 10.1111/jcmm.12625
|View full text |Cite
|
Sign up to set email alerts
|

The circulating transcriptome as a source of non‐invasive cancer biomarkers: concepts and controversies of non‐coding and coding RNA in body fluids

Abstract: The gold standard for cancer diagnosis remains the histological examination of affected tissue, obtained either by surgical excision, or radiologically guided biopsy. Such procedures however are expensive, not without risk to the patient, and require consistent evaluation by expert pathologists. Consequently, the search for non-invasive tools for the diagnosis and management of cancer has led to great interest in the field of circulating nucleic acids in plasma and serum. An additional benefit of blood-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 191 publications
(173 reference statements)
0
59
0
Order By: Relevance
“…In this section, we give a few examples of specific circulating miRNAs that have been shown to be altered in the plasma of hematological cancer patients. The oncogenic role of especially miR‐21, miR‐155, miR‐150, and miR‐210 are well established in hematological malignancies (Fabbri et al ., 2008; Fernandez‐Mercado et al ., 2015; Munker and Calin, 2011). In 2008, Lawrie et al .…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we give a few examples of specific circulating miRNAs that have been shown to be altered in the plasma of hematological cancer patients. The oncogenic role of especially miR‐21, miR‐155, miR‐150, and miR‐210 are well established in hematological malignancies (Fabbri et al ., 2008; Fernandez‐Mercado et al ., 2015; Munker and Calin, 2011). In 2008, Lawrie et al .…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%
“…EVs participate in cell–cell communication and can typically be classified based on their size (from 4 to 10 microns), intracellular origin, and density (Cocucci and Meldolesi, 2011; Raposo and Stoorvogel, 2013; Valadi et al ., 2007). EVs can be found in all different body fluids, such as blood, serum, plasma, saliva, urine, and pleural effusions (Fernandez‐Mercado et al ., 2015; Liu et al ., 2017a; Mitchell et al ., 2008; Ortiz‐Quintero, 2016; Weber et al ., 2010). In the last decade, several studies have shown that EVs are enriched for various proteins, such as cytokines, messenger RNAs, lipids, and noncoding RNAs, such as miRNAs and long noncoding RNAs (lncRNAs) (Colombo et al ., 2013; Valadi et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, the transcriptome offers the opportunity to analyze genes that are being actively expressed. 36 A handful of miRNA-based tests aimed at guiding therapeutic management have been already approved by FDA for applications such as classification of cancer of unknown primary origin (CUP), lung cancer type classification, thyroid cancer stratification, and breast cancer metastasis and recurrence analysis, based on the differential expression of miRNA biomarker sets. [37][38][39][40][41][42][43][44][45] Unlike the tests for viral RNA, which are offered as kits with a companion platform, cancer testing is offered as a service to healthcare providers.…”
Section: Fda-approved Rna Assays and Platformsmentioning
confidence: 99%
“…Table 1), 47 amplified cDNA samples, and one NTC from preassay amplification. A set of 285 amplified cDNA samples (including the pilot 47; IFC 2-4) and a subsequent set of 631 amplified cDNA samples (including all previous samples; IFC [5][6][7][8][9][10][11], were assayed on 96 3 96 arrays with an NTC on each array. Assays on these arrays included the pilot 48 target panel, supplemented with 25 additional candidate RNA biomarkers (Supplemental Table 1) and a second well for 23 targets to evaluate intra-array variation.…”
Section: Preassay Cdna Amplificationmentioning
confidence: 99%
“…In either application, the ability to profile short miRNA and long mRNA targets in the same panel would provide an efficient means to relate miRNA regulatory effects to mRNA expression, 4 or to profile both kinds of RNA biomarkers in the same biologic sample. 5 Fluidigm (South San Francisco, CA, USA) dynamic arrays use microfluidics [an "integrated fluidic circuit" (IFC) connected to reagent input wells] and high-resolution imaging to perform qPCR with fluorescence detection in nanoliter reaction volumes. 6,7 IFC formats include 12 3 12 (12 cDNA samples tested for each of 12 targets in individual parallel reactions), 48 3 48, 96 3 96, and 192 3 24.…”
Section: Introductionmentioning
confidence: 99%